(untitled) (Economics and region, 2025)
The article examines public–private partnership as a mechanism for intensifying entrepreneurial activity and advancing social innovation under conditions of globalization and digital transformation. The research problem is the lack of an integrated view of how institutional interaction between the public and private sectors translates into entrepreneurial outcomes and socially relevant results beyond traditional infrastructure logic. The aim is to assess the potential of public–private partnership to stimulate entrepreneurship and social innovation by means of bibliometric mapping of the scientific field and a systems interpretation of the revealed structures. Methodologically, the study applies bibliometric cartography of Scopus publications using VOSviewer (overlay and network visualizations) in combination with a systems approach that distinguishes institutional-legal, financial-organizational, innovation-entrepreneurial, educational-knowledge and sectoral subsystems. The mapping identifies a two-core configuration connecting public–private partnership with entrepreneurship via innovation, five stable thematic clusters, and three robust cross-cluster trajectories. Temporal layering indicates a shift from predominantly institutional and sectoral applications toward an emphasis on social value, sustainable development and social entrepreneurship. The findings also underline sectoral moderation: domains with established accountability and legitimacy regimes (notably health and transport) yield more predictable results, while high-uncertainty areas require more flexible contractual solutions and broadened success indicators. For Ukraine, the results substantiate the priority of institutional support: unified standards for project preparation and assessment, model contracts with clearly specified risk profiles, widened competitive access, blended-finance instruments, and transparent reporting with social metrics - measures that increase the likelihood that partnership impulses will materialize as innovation, new business opportunities and durable societal effects in recovery and smart-specialization agendas.